Analysis of human resource development strategies through training at Bank Syariah Indonesia - Apri Wigatiningrum; Pompong Budi Setiadi (Jurnal Mantik, 2023)
Banking organizations' efforts to have quality human resources are by developing human resources through training programs. Training is carried out to improve the competency, insight and attitudes of employees in the company to meet the company's current and future needs. The aim of this research is to analyze human resource development strategies through training at Bank Syariah Indonesia. In this research, the researcher tried to collect relevant sources, namely by using interviews, observation and documentation methods that are descriptive qualitative in nature. The results of this research show (1) The Human Resources Development Strategy in the Service Department at BSI KCP Mojokerto Gajah Mada is significant in implementing the development strategy using training methods, career development and the latest product updates to develop improvements in Human Resources in the Service Department. And (2) improving employee performance in the Service section at BSI KCP Mojokerto Gajah Mada providing various efforts, namely providing appreciation, motivation, bonuses, promotions and training, for employees who have increased performance. The development of the quality of Bank Syariah Indonesia's human resources is given great attention by providing continuous training to all employees to improve the quality and competency of their human resources